Interaksi Subak Jatiluwih dengan Pariwisata - PUTRI, NI LUH PUTU DIAH AYU HARTARI; SUDARTA, WAYAN; SURYAWARDANI, I GUSTI AYU OKA (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.6, No.4, Oktober 2017DO - 10.24843/JAA.2017.v06.i04.p06, 2017)
Subak of Jatiluwih Interaction with Tourism Jatiluwih is well known as a world-recognized agricultural and tourism area. This condition reflects a good interaction between agriculture which in this case is represented by subak/organization of irrigation with tourism i.e. is represented by tourism actors. Data collection in the field shows different conditions, namely the finding of land conversion and job transformation from subak members. Both of these conditions indicate an interaction between subak and tourism actors. The purpose of the study discusses the form of interaction between subak with tourism in Jatiluwih, and the impact of interaction on the existence of subak. The analytical method used to discuss the research problem is descriptive qualitative analysis. Qualitative descriptions are applied to information provided by the subak members and tourism stakeholders. The findings showed that associative interaction was more prominent than the dissociative interaction. Cooperation of Subak Jatiluwih with tourism in the permission of utilizing the subak area for the agency management of Jatiluwih Tourism Destination Area is meant to be the generator income because of its natural beauty. In contrast, Subak Jatiluwih needs for compensation for any damages to rice field and fund for religious ceremony of subak, namely the ceremony of Ngusaba Ayu and fund for cleaning the subak irrigation channel. The dissociative interaction can still be declared low because it can still be well anticipated. Suggestions that can be given that the contribution to the subak need to be considered for the subak given a more feasible contribution because it is considered so far not meet the feasible criteria.